Influence Mechanism of Rubber Thermal Oxygen Aging on Dynamic Stiffness and Loss Factor of Rubber Isolation Pad - Junjie Chen; Xian Li; Changyao Chen; Chaofeng Yang; Xiangdong Gao (International Journal of Polymer Science)
The influence mechanism of thermal oxygen aging on the dynamic characteristic of the rubber isolation pad (RIP) is usually ignored in studies. However, the ambient temperature of the RIP could reach up to 70°C in general, and even 108°C under some extreme conditions, which will lead to accelerated thermal oxygen aging and a decline in the mechanical performance for the RIP. In the meantime, the thermal oxygen aging will result in excessive vibration and even a damaged external air conditioner. Therefore, the research on the influence mechanism of rubber thermal oxygen aging on the dynamic performances of the RIP is crucial to the mechanical characteristic matching of the RIP. Considering the effect of the thermal oxygen aging on the dynamic characteristic, a novel model of thermal oxygen aging-dynamic characteristic of the RIP is established by adopting the Peck model, the hyperelastic model, the fractional derivative model, and the smooth Coulomb friction model (SCFM) in this paper. A test rig of the static and dynamic characteristics of the RIP is built, and an identification method of model parameters is developed based on the MTS831 elastomer test system as well which of the thermal oxygen aging-dynamic characteristic model is verified by the experimental data. The result is shown that the maximum growth rate of the static stiffness and the dynamic stiffness is 20.7% and 4.5%, respectively, and the maximum decrease rate of the loss factor is 10.6% as the thermal oxygen aging hardness of the RIP increases by 5HA. The amplitude-dependent, frequency-dependent, and thermal oxygen aging-dependent performances of the RIP are effectively characterized by the thermal oxygen aging-dynamic characteristic model. Moreover, a theoretical foundation is provided for the evolution law of the dynamic characteristic of the RIP after the service with the thermal oxygen aging condition in this research.